DEGRADASI MANGROVE SUATU ANALISIS BIBLIOMETRIK DAN TINJAUAN LITERATUR SISTEMATIS - Mohamad, Nurdin (Jurnal Biogenerasi, 2025)
Objectives: To analyze global research patterns on mangrove degradation through bibliometric analysis and systematic literature review to identify intellectual structure, temporal evolution, collaboration networks, and critical research gaps.Methods: Bibliographic data from Scopus and Web of Science (2000-2025) bbwere analyzed using VOSviewer and Biblioshiny for 1,247 publications. A total nof 156 high-quality articles underwent systematic review following PRISMA guidelines with co-citation, co-authorship, keyword co-occurrence analyses, and thematic synthesis.Results: Publications exhibited exponential growth (CAGR 12.3%) from 23 articles (2000) to 243 articles (2024) with 38,427 total citations. Asia-Pacific dominated (54%), followed by Latin America (23%) and Africa (15%). Australia, USA, and UK served as primary collaboration hubs. Six thematic clusters emerged: anthropogenic drivers (28%), climate change impacts (22%), ecosystem services valuation (19%), restoration strategies (16%), biodiversity conservation (10%), and tourism impacts (5% with fastest growth). Aquaculture conversion dominated (42% of studies), followed by infrastructure (31%), resource exploitation (28%), tourism (18%), and climate change (15%). Critical gaps: socio-economic integration (23%), economic valuation (8%), cumulative impacts (12%), and long-term monitoring (15%).